Bitter Falls - Caine, Rachel (Caine, Rachel. Stillhouse Lake series., 2020)
In spite of a harrowing past still haunting her, Gwen Proctor is trying to move forward. Until a new assignment gives her purpose: the cold-case disappearance of a young man in Tennessee. Three years missing, no clues. Just Ruth Landry, a tortured mother in limbo. Gwen understands what it<U+2019>s like to worry about your children. Gwen<U+2019>s investigation unearths new suspects- and victims. As she follows each sinister lead, the implications of the mystery grow more disturbing. Because the closer Gwen gets, the closer she is to a threat that looms back home. In a town that<U+2019>s closed its ranks against Gwen; her partner, Sam; and her kids, there<U+2019>s no bolder enemy than the Belldene family- paramilitary, criminal, powerful, and vengeful. As personal vendettas collide with Gwen<U+2019>s investigation, she<U+2019>s prepared to fight both battles. But is she prepared for the toll it could take on everyone she loves?